Pengaruh Terapi Meditasi Pernafasan Terhadap Tekanan Darah pada Lansia Di Kelurahan Karangmekar Wilayah Kerja Puskesmas Cimahi Tengah - Oyoh, Oyoh; Aini, Risyda; Dewi Rahmayanti, Siti; Rohayani, Lilis (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
Background; Hypertension is the main cause of cardiovascular disease in the elderly. The Cimahi City Health Office (2022) recorded 4,949 cases of hypertension at the Central Cimahi Health Center. One complementary therapy that can lower blood pressure is meditation therapy. Objective; Meditation therapy is a relaxation activity by focusing and clearing the mind so as to make yourself calmer and more relaxed. Knowing the effect of breathing meditation therapy on the elderly in Karangmekar Village, working area of Cimahi Tengah Health Center. Method; Using quasy-experiment research design with time series design approach. The sampling technique used was purposive sampling with a sample of 15 elderly respondents. The instruments used are a digital sphygmomanometer and standard operating procedures (SOPs) for meditation. Results: Univariate analysis with median value of systole blood pressure pre test: 151 mmHg and post test: 144 mmHg. In diastole blood pressure median pre test value: 95 mmHg and post test : 90 mmHg. The results of the Wilcoxon test on 15 respondents obtained a p value = 0.001 in systolic and in diastolic p value = 0.001. The conclusion seen from the value of p = 0.001 α of giving respiratory meditation therapy to the elderly in Karangmekar Village, the working area of the Central Cimahi Health Center. Conclusion; Suggestion It is hoped that respiratory meditation therapy can be used as one of the management of hypertension as a companion therapy for pharmacological treatment to lower blood pressure at the Central Cimahi Health Center.